(untitled) (Boletin Médico de Postgrado, 2023)
This essay aims to reflect on the study categories of an investigation that claims the theory of complexity and the methodological orientation that, from this position, guides the approach to the study phenomenon in a doctoral thesis; its purpose being to generate a theoretical model for public health on the systems of values ​​and meanings that promote participation in health and that can potentially be in favor of the construction of local development. From a hermeneutic-interpretative approach, with a bibliographic documentary method, it begins by proposing the position in the epistemic field, through a reflection on the theoretical aspects that support it. It concludes by addressing the explanation about how each of the study categories and proposed constructs will be seen and treated, for a specific human group in its specific historical moment, in an attempt to build a contextualized scientific proposal.